The Link Between Masculinity and Spatial Skills Is Moderated by the Estrogenic and Progestational Activity of Oral Contraceptives - Beltz, Adriene M.; Loviska, Amy M.; Kelly, Dominic P.; Nielson, Matthew G. (Frontiers in Behavioral Neuroscience, 2022)
Conversations about gender and spatial skills frequently dissolve into a hackneyed debate over nature and nurture. This is particularly true for conversations concerning three-dimensional (3D) mental rotations skill, which shows the largest gender difference of all aspects of cognition, with men—on average—outperforming women. To advance this empirical area of inquiry, biopsychosocial influences on spatial skills should be considered, and a unique opportunity do to that is provided by combined oral contraceptives (OCs). OCs with relatively low estradiol doses and with highly androgenic progestins have been positively related to spatial skills. Gender self-concepts, including masculine and feminine self-perceptions, have also been positively related to spatial skills. It is wholly unknown, however, whether the exogenous sex hormones contained in OCs moderate the link between self-perceived masculinity and 3D mental rotations. This study filled that knowledge gap by utilizing a sample of 141 naturally cycling (NC) women and 229 OC users who completed a computerized survey and cognitive tests. A series of moderation analyses examined whether the link between masculinity and 3D mental rotations depended on pill use or on the estrogenic, progestational, or androgenic activity in OCs, which were operationalized using a novel coding scheme. Results showed that the positive masculinity-3D mental rotations link was only present for NC women, presumably because it was altered by the exogenous hormones in OCs. Indeed, the link was accentuated in users of OCs with relatively low estrogenic and high progestational activity. Future research on menstrual cycle and pill phase is needed, but these findings importantly delineate ways in which biological and psychosocial factors combine to explain variation in spatial skills among women. They also suggest that focus should be placed on the under-investigated progestational activity of OCs, which is facilitated by the novel quantification of OC action used in this study. Thus, this research increases understanding of the neurocognitive and behavioral correlates of ovarian hormones and has implications for the betterment of women’s health.